(untitled) (Proceedings of the International Conference on Public Health, 2019)
The most common method of forensic identification is dental, fingerprint, and DNA. However those have a limitation such as high price , and limited cases. Palatal fold (rugae) and lip print pattern are a unique, stable and resistant morphological landmark foridentification. The purpose of this study is to examine the characteristic of rugae palatina and lip print pattern and the resemblance to the Minangkabau family relationship. This cross-sectional study, in 27 pure blood Minangkabaunese families. The sample was taken randomly. Palatal rugae was extracted from alginate printing. Lip print was taken on white paper after lips colored with red lipstick. IBM SPSS 17 is used for statistical analysis. The results show that there is similarity of rugae palatina based on family relationship. The circular male rugae has similarities to that of the father (p <0.05). Circular rugae in girls is derived from the mother, wavy ones are derived from both parents (p <0.05).. Lip print pattern doesn’t show the significant result. Conclusion is similarities of rugae palatina are influenced by genetic factors. Rugae palatina is good alternative identification method in forensic science. Palatal rugae pattern can be considered to be taken in routine dental medical record.